Introduction to the chemistry of food - Zeece, Michael (Academic Press, 2020)
Introduction to the Chemistry of Food describes the molecular composition of food and the chemistry of its components. It provides students with an understanding of chemical and biochemical reactions that impact food quality and contribute to wellness. This innovative approach enables students in food science, nutrition and culinology to better understand the role of chemistry in food. Specifically, the text provides background in food composition, demonstrates how chemistry impacts quality, and highlights its role in creating novel foods. Each chapter contains a review section with suggested learning activities. Text and supplemental materials can be used in traditional face-to-face, distance, or blended learning formats